Palaeoenvironmental reconstruction of late Holocene climate dynamics in Southwest Africa using a multi-proxy characterization of Namaqualand mudbelt sediments - Granger, Robyn (Department of Environmental and Geographical Science, 2016)
Despite the recognized importance of understanding late Holocene climatic changes in southern Africa, a dearth of available evidence has resulted in a frag- mented view of the recent past. South Africa has been identified as a key focus region for palaeoclimatic studies, as it reflects the dynamics of both tropical and temperate climate regimes. This study aims to create a catchment-integrated view of palaeoenvironmental conditions in the country's Winter Rainfall Zone (WRZ) and Southern Benguela region during the late Holocene, in order to establish the linkages between oceanic and terrestrial climate components. A multiproxy analysis was conducted on a west coast mudbelt sediment core, where continuous deposition over the last 2,250 years has aided the production of an uninterrupted age model. Alkenone and isotopic analyses were conducted at a multi-decadal resolution to assist in the reconstruction of sea-surface tem- perature (SST) in the St. Helena Bay region, and hydrological variation in the WRZ. Changes in moisture availability were inferred via the application of in- organic proxies, including grain size variation (promoted through the use of an end-member proxy algorithm) and the Fe/K ratio, a proxy interpreted to be rep- resentative of changes in chemical weathering. Furthermore, a newly-developed proxy, TEX 86 , was used as an alternative palaeothermometer. TEX 86 produced an additional record of SST, independent of alkenones, which elicited a com- parative study between SST TEX86 and SST UK'37 . The comparison facilitated a review of the effectiveness of TEX 86 within the Benguela Upwelling System, and assisted in quantifying reasons for the observed differences between the two methods. The results of the multiproxy analysis sheds new light on southwest African late Holocene climatic dynamics. This study documents a decrease in SST accompanied by increasing WRZ rainfall, which is hypothesized to be a result of large-scale changes in the position and/or intensity of the austral westerly wind belt. A northerly migration/increase in intensity of the winds acts to produce cooler SSTs and wetter west coast continental conditions, both of which were most acutely experienced during the so-called Little Ice Age (LIA) (1300 - 1850 CE). Zonal symmetry across the Southern Hemisphere is hypothesized to be a consequence of the large geographical extent of the westerly winds, as cooler and wetter conditions have been experienced in coastal, winter-rainfall areas of Chile and Australia.